Derecho y Literatura: Textos y Contextos. Jorge Roggero (2015). Buenos Aires: Eudeba - Santos López, Danilo; Urgelles Latorre, Ingrid (Iuris Dictio, 2016)
Derecho y Literatura: Textos y Contextos. Jorge Roggero (2015). Buenos Aires: Eudeba.